Perbandingan analisis studi kelayakan usaha hasil peramalan simulasi monte carlo dengan kondisi sebenarnya - Oktavia, Chendrasari wahyu; Subaderi, Subaderi; Alfarizi, Ahmad; Arrosyid, M Ferdy (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Every laundry business owner certainly wants to know how far the business they have run has developed. To find out this, a business feasibility study is needed that looks at the aspects of revenue and total costs. However, unfortunately, business actors do not carry out business feasibility study calculations. Therefore, this research aims to analyze the extent of business development in the coming period. The approach used is Monte Carlo simulation to calculate the amount of revenue in the future period and the R/C ratio is calculated and the actual condition results are also calculated by the R/C ratio to obtain comparative results. Based on the R/C ratio results with simulation revenue results, it shows that the laundry business in February and April was above 1, which means it experienced a profit and vice versa, with actual conditions in February and March below 1, which means it experienced a loss.